DIAGNOSTIC VALUE OF LABORATORY TESTS OF WOMEN IN THE DYNAMICS OF TREATMENT OF PERIODONTAL DISEASES CONCOMITANT WITH BACTERIAL VAGINOSIS - T.O. Petrushanko; A.D. Krutikova; E.I. Krutikova (Проблеми екології та медицини)
The lack of clear dental screening strategy for women with bacterial vaginosis (BV) leads to inadequate treatment planning, since atypical triggering factors are not considered, despite the given evidence for the presence of chronic generalized inflammatory and inflammatory-dystrophic periodontal diseases in patients with BV. The analysis of the oral fluid, especially its protective properties, is crucial in the noninvasive diagnostics. In this regard, alpha-amylase and secretory IgA (sIgA) are noteworthy. The aim of the research. The paper was aimed at verification of the diagnostic value of the assessment of the outcomes of the recent treatment of inflammatory and inflammatory-dystrophic periodontal diseases in women of reproductive age with bacterial vaginosis by determining the changes in the kinetic activity of alpha- amylase and sIgA concentration. Material and Methods. 50 women of reproductive age have been examined. The subjects were assigned into groups according to their gynecological status: Group I (control) (n=10) included women with the I and II degree of purity of the vagina Group II (n=10) included carriers of Gardnerella vaginalis without diagnosed bacterial vaginosis ; Group ІІІ-A (n=15) included women with verified diagnosis of BV who received conventional treatment; Group IІІ-B (n=15) included women with BV, who received treatment using our patented treatment regimen that takes into account the presence of specific BV-microflora found in the oral cavity in this group of subjects. In the oral cavity the results of the amino-test of the oral fluid were analyzed and kinetic activity of alpha-amylase and sIgA concentration was determined. The presence of Gardnerella vaginalis and Atopobium vaginae in the oral cavity was determined by the polymerase chain reaction (PCR) method. Results. The sIgA level of women with BV was by 30-45% lower as compared to the value of patients without BV. Concentration of oral sIgA in both groups of women was restored after treatment, but the results of the III-A and III-B groups after treatment significantly differed (the result of sIgA in subjects of Group III-B was by 1.33 times higher than the value of Group III-A), indicating the higher efficacy of the proposed treatment regimen, which takes into account the presence of etiological agents of BV in the oral cavity. The results of the amino test of oral fluid were positive in patients of Group III-A before treatment in 73.3%, after treatment only in 53.3%, while in the subjects of Group III-B the initial result was 80%; after treatment, a decrease to 20% was registered. Conclusions. The diagnostic value of the applied laboratory methods for examination of local resistance in women is sufficient for mass use as a control of the results in periodontal treatment of patients with inflammatory and inflammatory-dystrophic periodontal diseases concomitant with bacterial vaginosis.